care and Harm Reduction as health promoters in the territory of Cracolândia - Camargo, Paola de Oliveira (2020)
This study was searchi comprehend the questions about the conditions of healf and disease of the people who use drugs and / or are homeless in the territory of Cracolândia. Participant observation and field diary construction were performed, as well as ethnographic interviews with participants. These were the people who were in the territory of Cracolândia and the damage reducers who worked there. For data analysis we used Interpretativism, or Interpretive Theory. The results showed that the territory of Cracolândia can present circumstances that generate diseases, but also be a place of health promotion and care.